Reliability of a sleep quality questionnaire for use in epidemiologic studies - Girschik, J.; Heyworth, J.; Fritschi, Lin (British Medical Journal Group, 2012)
Background: The longer-term health impacts of poor sleep quality are of increasing interest, as evidence suggests that there are rising levels of sleep disturbance in the community. Studies have reported links between sleep quality and increased morbidity and mortality. However, the results of these studies are constrained by limitations in the measurement of sleep quality in epidemiologic studies. The Breast Cancer Environment and Employment Study (BCEES) has developed a sleep questionnaire that attempts to address some of the limitations of previous sleep questionnaires. The present study assessed the test-retest reliability of the sleep questionnaire used in the Breast Cancer Environment and Employment Study (BCEES). Methods: Subjects for this reliability study were women who were participating as controls in the BCEES study. Test-retest reliability was evaluated for individual items, using weighted kappa for categorical variables and intraclass correlation coefficients (ICC) and limits of agreement for continuous variables. Results: Most sleep questions showed good agreement, ranging from 0.78 to 0.45. The ICC was 0.45 (95% CI 0.32–0.59) for lifetime sleep loss per year and 0.60 (95% CI 0.49–0.71) for symptom severity. Conclusions: The test-retest reliability of the general sleep questions was good, and future epidemiologic studies of sleep could reliably expand the number of assessed domains of sleep quality. However, reliability decreased as increasing detail was required from participants about specific periods of sleep disturbance, and changes to the questionnaire are warranted.